2008
DOI: 10.1029/2007jd008920
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the intrinsic frequency and other wave parameters from a single vertical temperature or density profile measurement

Abstract: [1] In order to examine internal gravity wave characteristics we have analyzed small-scale fluctuations of normalized temperature in the Earth's stratosphere using radio occultation data. An analysis to identify the observed fluctuations as wave-induced, assuming gravity wave shear saturation, is proposed. This technique is based upon a comparison of the experimental and theoretical values of the relative amplitude threshold which is defined as the wave amplitude required for shear instability. The theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 16 publications
1
57
0
Order By: Relevance
“…Wang and Alexander (2010) and McDonald (2012), analyzing collocated temperature profiles from COSMIC observations, showed that in the stratosphere, the most large-scale dominant temperature perturbations are of wave nature. Gubenko et al (2008Gubenko et al ( , 2011 developed a method for the determination of the basic characteristics of dominant IGWs, including their intrinsic frequency and phase velocities from vertical profiles of temperature. The method was validated on high-resolution radiosonde observations of temperature and wind and then applied to the analysis of IGWs based on temperature profiles retrieved from RO observations in COSMIC and CHAMP missions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and Alexander (2010) and McDonald (2012), analyzing collocated temperature profiles from COSMIC observations, showed that in the stratosphere, the most large-scale dominant temperature perturbations are of wave nature. Gubenko et al (2008Gubenko et al ( , 2011 developed a method for the determination of the basic characteristics of dominant IGWs, including their intrinsic frequency and phase velocities from vertical profiles of temperature. The method was validated on high-resolution radiosonde observations of temperature and wind and then applied to the analysis of IGWs based on temperature profiles retrieved from RO observations in COSMIC and CHAMP missions.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of GPS signals, complemented with its global coverage and high vertical resolution, draws the attention of researchers to the study of inhomogeneities in atmospheric refractivity in addition to the retrieval of mean profiles (Belloul and Hauchecorne, 1997;Gurvich et al, 2000;Tsuda et al, 2000;Wang and Alexander, 2010;Cornman et al, 2004Cornman et al, , 2012Shume and Ao, 2016;Gubenko et al, 2008Gubenko et al, , 2011. Occultation-based methods of sounding atmospheric inhomogeneities have a long and successful history.…”
Section: Introductionmentioning
confidence: 99%
“…Strong amplitude and phase frequency dependent variations in the RO signals are often surprisingly observed within the altitudes of the RO ray perigee () hT between 30 and 80 km above the main part of the neutral atmosphere and below the Elayer of the ionosphere. The effects of strong phase and amplitude variations of the RO signals at a low altitude provide a good source of information for the remote sensing of the atmosphere and ionosphere including detecting and studying the internal gravity waves propagating in the atmosphere and ionosphere [54]. Accurate knowledge of spatial location, height and inclination of the sporadic E-layers is important for the estimation of the offequatorial height-integrated conductivity [44,45].…”
Section: Application Of Gps Ro Methods To Study the Atmosphere And Ionmentioning
confidence: 99%
“…The radio occultation (RO) method employs the highly-stable radio waves transmitted at two GPS frequencies 1 f  1575.42 MHz and 2 f  1227.60 MHz by the GPS satellites and recorded at a GPS receiver onboard low Earth orbiting (LEO) satellite to remote sense the Earth's ionosphere and neutral atmosphere [4,5,10,11,17,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]46,47,[52][53][54][55][56][59][60][61]. When applied to ionospheric investigations the RO method may be considered as a global tool and can be compared with the global Earth-and space-based radio tomography [42,43].…”
Section: Application Of Gps Ro Methods To Study the Atmosphere And Ionmentioning
confidence: 99%
“…In this section, we present a comparison between the normalized density perturbations resulting from the polynomial fits of N 2 (z) and the fit of the temperature profile with a cubic polynomial as used, for example, by Gubenko et al (2008). We have computed the mean vertical wave-number power spectrum for the sample of 60 profiles.…”
Section: In the Stratospherementioning
confidence: 99%